1993
DOI: 10.1038/bjc.1993.319
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in cancer patients

Abstract: (Cristensen, 1989).To date there are few studies which systematically register how many cancer patients experience fatigue, in which stage of the disease process and to what extent. To give an indication, a literature-search using MEDLINE with CD-ROM over the period 1980 to 1991 yielded nine references in which 'fatigue' was included in the title and 'cancer' was included in title, keyword or abstract. Eight of these references pertained to nursing research.An appraisal of the research literature concerning fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
139
0
11

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(154 citation statements)
references
References 41 publications
1
139
0
11
Order By: Relevance
“…A study of patients with chronic fatigue syndrome found that those with high levels of fatigue performed less well on a memory task even in the absence of depression (McDonald et al, 1993). Fatigue is a common complaint among cancer patients during treatment (Smets et al, 1993) and among Hodgkin's disease patients in remission (Fobair et al, 1986 [1][2][3][4] (not at all to very much) and combined to form the cognitive functioning scale on which linearly transformed scores ranged from 0 to 100. Overall health and quality of life are each rated 1-7 (very poor to excellent) and combined to form a global health status/QL scale that, with linear transformation, also ranges from 0 to 100.…”
mentioning
confidence: 99%
“…A study of patients with chronic fatigue syndrome found that those with high levels of fatigue performed less well on a memory task even in the absence of depression (McDonald et al, 1993). Fatigue is a common complaint among cancer patients during treatment (Smets et al, 1993) and among Hodgkin's disease patients in remission (Fobair et al, 1986 [1][2][3][4] (not at all to very much) and combined to form the cognitive functioning scale on which linearly transformed scores ranged from 0 to 100. Overall health and quality of life are each rated 1-7 (very poor to excellent) and combined to form a global health status/QL scale that, with linear transformation, also ranges from 0 to 100.…”
mentioning
confidence: 99%
“…Following cancer diagnosis, treatments such as surgery, radiotherapy or chemotherapy may induce fatigue. It is estimated that about 70% of cancer patients experience fatigue during radiotherapy and chemotherapy (Smets et al, 1993). In general, fatigue decreases during the period of convalescence.…”
mentioning
confidence: 99%
“…Reliable and valid indicators of fatigue are necessary to study this symptom. Based on a review of instruments used in studies involving cancer patients it was concluded that most measures of fatigue in cancer are incorporated in instruments that measure broader aspects of patient functioning (Smets et al, 1993). Instruments that are more comprehensive and easy to administer and that have been thoroughly tested for their psychometric properties were found to be lacking.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] The cancer diagnosis and treatment characteristics are not related to postcancer fatigue. 6,[12][13][14][15][16] There is evidence, however, that patients who receive only surgery have a decreased risk for postcancer fatigue 11 and patients who receive both surgery and adjuvant treatment have an increased risk for postcancer fatigue. 7,17 Cognitive behavior therapy (CBT), particularly composed for postcancer fatigue, is proven to be efficacious in treating severely fatigued cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Already during cancer treatment 70-96% of the patients suffer from fatigue symptoms. 5,6 Postcancer fatigue has a prevalence ranging from 19 to 39% as observed in longitudinal studies. [7][8][9][10][11] The cancer diagnosis and treatment characteristics are not related to postcancer fatigue.…”
Section: Introductionmentioning
confidence: 99%